Idea ochrony Kanionu Colca i Doliny Wulkanów - Gałaś, Andrzej; Paulo, Andrzej (Wydawnictwa AGH, 2008)
Development of tourism and related infrastructure in the Rio Colca Canyon region endangers environment of this deepest canyon worldwide. There is urgent need of balancing landuse development by protection of the most valuable areas and proving their importance to the world heritage of nature. Studies performed by the Polish Scientific Expedition to Peru since 2003 are aimed at project of the Canyon Colca and Valley of Volcanoes National Park. This park should protect a unique section of the orogenic belt 100 km long and 1-3 km high, magnificient landscape, sets of active faults, volcanoes, hot springs and specific wildlife including the largest condor habitat in the Andes. New park would strenghten the state protected areas system in the Arequipa department, increase its tourist attractiveness and determine constraints of regional development. Local authorities show great interest in developing the project.

Rozwój turystyki oraz towarzyszący mu rozwój infrastruktury stanowią zagrożenie dla walorów środowiska w Kanionie Colca, który jest najgłębszym kanionem na świecie. Istnieje pilna potrzeba równoważenia tego rozwoju przez ochronę najcenniejszych obszarów i wykazanie ich znaczenia dla światowego dziedzictwa przyrody. Badania Polskiej Wyprawy Naukowej do Peru, prowadzone od 2003 roku, zmierzają do zaprojektowania Parku Narodowego Kanion Colca i Dolina Wulkanów. Park obejmie unikalny w skali świata przekrój pasma górskiego o długości ponad 100 km i wysokości 1-3 km, wspaniałe krajobrazy, zespoły aktywnych uskoków, fałdy, wulkany, gorące źródła oraz specyficzny świat roślin i zwierząt, w tym największe w Andach siedlisko kondorów. Utworzenie parku wzmocniłoby ubogi system obszarów chronionych w departamencie Arequipa, podwyższyło atrakcyjność turystyczną i wyznaczyło ramy rozwoju regionu. Władze regionalne są żywo zainteresowane rozwojem projektu.
Idea of protection of Rio Colca Canyon and Valley of Volcanoes
Geologia
Keywords: Peru; national park; environmental protection; Colca Canyon; Valley of the Volcanoes; buffer zone; sustainable development; parki narodowe; ochrona środowiska; Peru; Kanion Colca; Dolina Wulkanów; strefa buforowa; rozwój zrównoważony